Hortas escolares em Santarém: implementação, práticas, usos e situação atual - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The school gardens was implemented by government and private partnerships, at 2005 to 2010 on many basic education school on Brazil. The purposes were among other such as greenery production for school meals supply with security and healthy foods, the practical and interdisciplinar teaching and learning purposes. Eleven (11) basic education school was visited in Santarém, west region of Pará state, Brazil. The selected persons of each school were questioned about school gardens to investigate their project partnerships to implement and maintenance, to consumptions and uses of gardens products. The majority of them activated only one time and now are abandoned. One of the scarce successful case was selected to case study: The school garden of the SEARA Nursery school is in pause state, during the unfavorable dry season. When the favorable rainy season arrives on region, student’ mothers dedicate voluntarily to seeding and crop care needs. it was ‘not used to teaching/learning purposes and the scholar participations observed was very poor or absent. it is recommendable that a education project be adicioned to use school garden for teach and learn purpose as recommend the curricular parameters of brasilian education.
Keywords: Horta; Temas Transversais; Nutrição; Saúde; CNPQ:: CIÊNCIAS BIOLÓGICAS